Geo-Stem Integration and Environmental Literacy in Geography Education: A Systematic Review and Bibliometric Analysis - Abdul Mufahir; Bagja Waluya; Annisa Joviani Astari (Research, Training and Philanthropy Institution Natural Aceh, 2026)
Rapid urbanization, technological acceleration, and increasing environmental degradation have intensified the need to strengthen environmental literacy through geography education. However, previous studies tend to examine Geo-STEM integration and environmental literacy separately, with limited attention to how Geo-STEM contributes to meaningful learning and behavioral transformation. This study aims to systematically map Research trends, thematic patterns, and Research gaps related to the integration of Geo-STEM and environmental literacy in geography education. A Systematic Literature Review (SLR) combined with bibliometric analysis was conducted following PRISMA 2020 guidelines. Data were retrieved from the Scopus database, yielding 151 articles for bibliometric analysis and 29 for qualitative synthesis. VOSviewer was employed to analyze publication trends, keyword co-occurrence, and thematic clusters. The findings reveal a significant increase in Geo-STEM and environmental literacy Research after 2020, with three dominant clusters: geography education and learning outcomes, STEM-based pedagogy, and geospatial technologies such as GIS, remote sensing, and artificial intelligence. Nevertheless, gaps remain in linking Geo-STEM implementation to behavioral change and deep learning outcomes. This study contributes by synthesizing current evidence and proposing an integrative framework to support curriculum development, teacher capacity building, and sustainable geography education.